EFFECT OF TRAINING IN MORINGA PUDDING MAKING ON THE SKILLS OF CADRES IN THE COASTAL AREA OF KENDARI CITY - Sumarti, Sumarti; Tosepu, Ramadhan (Preventif Journal, 2024)
ABSTRACT Moringa leaf pudding is one type of additional food that is rich in nutrients. The nutritional content of moringa leaves includes protein, beta carotene (pro-vitamin A), carbohydrates, calcium, fiber, energy that can maintain health and stamina. Making moringa leaf pudding is quite easy, but the cadres do not have the skills to make moringa leaf pudding. The purpose of this study was to determine the effect of Moringa Leaf Pudding Making Training on Cadre Skills in the Coastal Area of Kendari City. Type of pre-experimental research with One Group pretest-posttest research design. The sample in this study were 16 cadres in the coastal area of Kendari City, namely cadres in Abeli Village using accidental sampling technique. Statistical tests using the Wilcoxon pSigned Rank Test. Data collection questionnaires and observation sheets. The results of the study obtained the value of skills before training is a mean of 4.88, a minimum of 3 and a maximum of 7 and the value after training obtained a mean of 7.39, a minimum of 5 and a maximum of 10. The results of the Wilcoxon test obtained a P value of 0.000. The conclusion of this study is that there is an effect of Moringa leaf pudding making training on cadres in the coastal area of Kendari City. It is hoped that cadres can utilize local food ingredients and process them into pudding and then distribute it to the community, especially mothers who have children under five. Keywords: Cadre, Moringa, Pudding, Skills